Menno Simons: A Cross-Denominational Legacy - Influences on Mennonite, Baptist, Methodist, and Adventist Church - Pane, Exson Eduaman; Krisminanto, Ferin (Jurnal Koinonia: Fakultas Filsafat Universitas Advent Indonesia, 2023)
The journal delves into the life and teachings of Menno Simons, a pivotal but often overlooked figure in the 16th-century Anabaptist movement. Despite not achieving the same prominence as contemporaries like Luther and Calvin, Simons significantly influenced the trajectories of Mennonite and related denominations. The study meticulously examines Simons' theological contributions, focusing on his ethical framework promoting responsible material possession use.Simons' bold decision to join the Anabaptist movement marked a stride towards religious freedom, leaving a lasting impact on Mennonite doctrinal development. The journal explores the interplay between Simons' teachings and his indirect influence on the Seventh-day Adventist Church, shedding light on his roles as a theologian, author, and educator. Through historical analysis and primary sources, it navigates Simons' life, emphasizing his early years, religious journey, and contributions.Comparing Simons' legacy across denominations like Mennonite, Baptist, Methodist, and Adventist, the study highlights commonalities and divergences in incorporating his teachings, especially regarding baptism, the Trinity, and Scripture. The journal underscores Simons' impact on various religions, causing concerns for the Holy Roman Emperor and leading to departures from the Roman Catholic Church. Detailed exploration of Simons' teachings and their subsequent influence on different denominations is provided, with a particular emphasis on his impact on baptism, the Trinity, and Scripture. Despite some shared beliefs, the study notes distinctions between Menno Simons' teachings and those of the Seventh-day Adventist Church. The exploration concludes by thoroughly examining Simons' lasting impact on Christian traditions, his influence on the Seventh-day Adventist Church, and his broader theological legacy, offering a nuanced perspective on his contributions and highlighting his courageous stand for religious freedom.